1981
DOI: 10.1161/01.res.49.2.442
|View full text |Cite
|
Sign up to set email alerts
|

Pulse wave propagation.

Abstract: This report evaluates pulse wave propagation with respect to contributions by vascular wall elastic and geometric properties, vessel wall and blood viscosity, and nonlinearities in system parameters and in the equations of motion. Discrepancies in results obtained with different experimental methods and theory are discussed and resolved. A three-point pressure technique was used to obtain measurements from the abdominal aorta, carotid, iliac, and femoral arteries of dogs. Computations involved linear, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…Calculation of input impedance is only permitted for linear systems. Although the linear behavior of the entire arterial tree has been challenged (Milnor and Nichols, 1975;Milnor and Bertram, 1978), several reports show that linearity is a reasonable assumption (Dick et al, 1966;Noble et al, 1967;Li et al, 1981). We have measured the input impedances before and during the interventions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Calculation of input impedance is only permitted for linear systems. Although the linear behavior of the entire arterial tree has been challenged (Milnor and Nichols, 1975;Milnor and Bertram, 1978), several reports show that linearity is a reasonable assumption (Dick et al, 1966;Noble et al, 1967;Li et al, 1981). We have measured the input impedances before and during the interventions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since blood viscosity is clearly a factor, a frequent starting point for modelling the flow in blood vessels (e.g. [8][9][10]) is Womersley's solution [11] for the oscillatory motion of a viscous fluid in a thin-walled elastic tube. In fact, many studies use simplified approximations of Womersley's velocity profiles, such as a Stokes layer near the boundaries with a central uniform core, a power law, the Poiseuille profile or even simply uniform flow [5].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in harmony with previous experimental studies where authors found attenuation values completely higher than the theoretical ones. Li et al (18) , who used transducer distance of 2-3 cm and Milnor et al (11), (24) , who used 3.5-5.3 cm, obtained attenuation values much higher than those predicted by linear theories when applying the three-point method. However, Ursino et al (22) , who used transducer distance of 10 and 40 cm and Reuderink et al (25) , who used transducer distance of 10 cm and found good agreement between calculated and theoretical values of propagation coefficient.…”
Section: Discussionmentioning
confidence: 92%
“…These methods, supposing a uniform artery with linear behaviour and the same phase velocity for the forward and backward waves, provide a true propagation coefficient. The merits, disadvantages and errors inherent in the determination of propagation coefficient by three-point and two-point method have been discussed by several authors (12), (13), (14), (18) . Results obtained by such methods are conflicting and led different groups to different conclusions especially concerning the three-point method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation